Integration of Non-Communicable Diseases in Health Care: Tackling the Double Burden of Disease in African Settings - Temu, Florence; Leonhardt, Marcus; Carter, Jane; Thiam, Sylla (Pan African Medical Journal and African Field Epidemiology Network (AFENET))
Sub-Saharan African countries now face the double burden of Non Communicable and Communicable Diseases. This situation represents a major threat to fragile health systems and emphasises the need for innovative integrative approaches to health care delivery. Health services need to be reorganised to address populations' needs holistically and effectively leverage resources in already resource-limited settings. Access and delivery of quality health care should be reinforced and implemented at primary health care level within the framework of health system strengthening. Competencies need to be developed around services provided rather than specific diseases. New models of integration within the health sector and other sectors should be explored and further evidence generated to inform policy and practice to combat the double burden.
© Sylla Thiam et al. The Pan African Medical Journal - ISSN 1937-8688. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/2.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Non-communicable diseases; Health care; Burden of disease; Africa